Synthesis and growth of rare earth borates NaSrR(BO3)2 (R = Ho− Lu, Y, Sc) - Kuznetsov, Artem B.; Kokh, Konstantin A.; Sagatov, Nursultan; Gavryushkin, Pavel N.; Molokeev, Maxim S.; Svetlichnyi, Valerii A.; Lapin, Ivan N.; Kononova, Nadezda G.; Shevchenko, Vyacheslav S.; Bolatov, Asset; Uralbekov, Bolat; Goreiavcheva, Anastasia A.; et al. (Inorganic chemistry)
NaSrR(BO3)2(R = Ho-Lu, Y, Sc) compounds were obtained for the first time. Their structures exhibit disordered positions of Sr2+and Na+ atoms while RO6polyhedra are connected through the BO3 groups. Large distances between R atoms and high transparency in the range of 250-900 nm make them promising for phosphor applications. A pathway to obtain single crystals was shown by growing NaSrY(BO3)2and NaSrYb-(BO3)2by the top seeded solution growth method with Na2O-B2O3-NaFflux.